The Effect of a BSA Conjugate of a Synthetic Hexasaccharide Related to the Fragment of Capsular Polysaccharide of Streptococcus pneumoniae Type 14 on the Activation of Innate and Adaptive Immune Responses - Akhmatova, Nelli K.; Kurbatova, Ekaterina A.; Akhmatov, Elvin A.; Egorova, Nadezhda B.; Logunov, Denis Yu.; Gening, Marina L.; Sukhova, Elena V.; Yashunsky, Dmitry V.; Tsvetkov, Yury E.; Nifantiev, Nikolay E. (Frontiers in Immunology, 2016)
We report the effect of a BSA conjugate of a synthetic hexasaccharide related to the fragment of the capsular polysaccharide (PS) of Streptococcus pneumoniae type 14 on the stimulation of innate and cell-mediated immunity and the subsequent development of a PS-specific antibody response. Glycoconjugate (GC) in the presence (GC+AL) or absence of aluminium hydroxide was administered to mice twice. GC increased the number of TLR2-expressing cells and induced the maturation of dendritic cells (CD11c+, CD80+ and MHCII+), which secreted IL-1β, IL-6, and TNFα into the culture medium. The level of IL-1β, IL-10, IFNγ, and TNFα in the blood increased within 24 h after the single GC administration to mice. On day 7, the numbers of splenic CD4+ and CD8+ Т lymphocytes and B lymphocytes increased. After the second immunization, the levels of CD4+ and CD8+ Т lymphocytes were lower than in the control, whereas the B cell, NK cell and MHC class II-expressing cell numbers remained enhanced. However, of the presence of anti-PS IgG antibodies was not detected. The addition of aluminium hydroxide to GC stimulated the production of GM-CSF, IL-1β, IL-5, IL-6, IL-10, IL-17, IFNγ, and TNFα. Anti-PS IgG1 antibody titres 7 days after the second immunization were high. During that period, normal levels of splenic CD4+ T lymphocytes were maintained, whereas reduced CD8+Т lymphocyte numbers and increased levels of B lymphocytes, NK cells and MHC class II-expressing cell numbers were observed. Anti-PS IgG levels diminished until day 92. A booster immunization with GC+AL stimulated the production of anti-PS IgG memory antibodies, which were determined within 97 days. The elucidation of specific features of the effect of the synthetic hexasaccharide conjugate on the stimulation of innate, cell-mediated immunity and antibody response can favour the optimization of glycoconjugate vaccine design.